Increasing Student Collaboration Through the Scramble Type Cooperative Learning Model in Elementary School - Yossa Kandya (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: Learning that prioritizes one-way interaction in class causes the learning process to become less interesting so that students easily get bored when participating in learning activities. This research aims to increase student cooperation through the Scramble type cooperative learning model in class III students at State Elementary School 187/1 Muara Bulian. Methodology: This research is classroom action research which consists of two cycles, where the data taken is in the form of observation data, through student collaboration observation sheets. This research was carried out in 4 stages, namely the planning, implementation, observation and reflection stages. During the teaching and learning process, learning activities apply the Scramble type cooperative learning model. Main Findings: The research results show that the application of the Scramble type cooperative learning model can increase student cooperation in social studies subjects. Based on the observation sheet, student collaboration shows an increase with the percentage of student collaboration being 69% in the good category in cycle I and 84% in the very good category in cycle II. Based on the research findings, it can be concluded that student cooperation in social studies learning for class III students at State Elementary School 187/I Muara Bulian can increase after implementing the Scramble type cooperative learning model. Novelty/Originality of this study: This research shows a significant increase in student collaboration after implementing this learning model. These findings indicate that the Scramble type cooperative learning model is effective in encouraging student cooperation and making the learning process more interesting for them. Thus, this research contributes to the development of learning methods that are more interactive and actively involve students.